Color Centers in BaFBr Crystals: Experimental Study and Theoretical Modeling - Inerbaev, Talgat; Akilbekov, Abdirash; Kenbayev, Daurzhan; Dauletbekova, Alma; Shalaev, Alexey; Polisadova, Elena; Konuhova, Marina; Piskunov, Sergei; Popov, Anatoli I. (MDPI, 2024)
This study presents theoretical and experimental investigations into the electron and hole color centers in BaFBr crystals, characterizing their electronic and optical properties. Stoichiometric BaFBr crystals grown by the Steber method were used in the experiments. Radiation defects in BaFBr crystals were created by irradiation with 147 MeV 84Kr ions with up to fluences of 1010–1014 ions/cm2. The formation of electron color centers (F(F−), F2(F−), F2(Br−)) and hole aggregates was experimentally established by optical absorption spectroscopy. Performed measurements are compared with theoretical calculations. It allows us to determine the electron transition mechanisms and investigate the processes involved in photoluminescence emission in Eu-doped BaFBr materials to enhance the understanding of the fundamental electronic structure and properties of electron and hole color centers formed in BaFBr crystals. © 2024 by the authors. --//-- This is an open-access article Inerbaev, T.; Akilbekov, A.; Kenbayev, D.; Dauletbekova, A.; Shalaev, A.; Polisadova, E.; Konuhova, M.; Piskunov, S.; Popov, A.I. Color Centers in BaFBr Crystals: Experimental Study and Theoretical Modeling. Materials 2024, 17, 3340. https://doi.org/10.3390/ma17133340 published under the CC BY 4.0 licence.
This research was funded by the Ministry of Education and Science of the Republic of Kazakhstan, grant number AP14870572 \u201CExperimental-theoretical analysis of processes induced by radiation defects in scintillation materials for nuclear and space applications\u201D. In addition, the research of A.I.P. was partly supported by COST Action CA20129 \u201CMultiscale irradiation and chemistry driven processes and related technologies\u201D (MultiChem). Furthermore, the research of A.I.P and MK was partly supported by Latvian State Research Programme on Nr. VPP-IZM-CERN-2022/1-0001 and Latvian Research Project lzp-2023/1-0453. ISSP UL as the Center of Excellence, is supported through the Framework Program for European Universities, Union Horizon 2020, H2020-WIDESPREAD-01\u20132016\u20132017-TeamingPhase2, under Grant Agreement No. 739508, CAMART2 project.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; color centers; density functional theory (DFT); optical absorption; single crystal BaFBr; swift heavy ions; VASP